Pembelajaran Metode Drill Untuk Meningkatkan Hasil Belajar Passing Bawah Pada Permainan Bolavoli Siswa SMPN 2 Mare Kabupaten Bone - Andi Amry Yahya; Sufitriono Sufitriono (Universitas PGRI Semarang, 2020)
Drill Learning Method To Improve Lower Passing Learning Outcomes in Volleyball at SMPN 2 Mare BoneThis study aims to determine the effect of the Drill learning method and the conventional learning method on the learning outcomes of passing under the volleyball game of students of SMPN 2 Mare Bone District. This research method is a type of experimental research chosen by random sampling and then given a pretest and posttest with a population of all students of SMPN 2 Mare Bone District. Next class VIIIA and class VIIIB were chosen to be the sample of this study, each numbering 30 students and then divided into two groups using ordinal paired maching. data analysis techniques used t test with a significance level of 0.05.The results of this study show there is a significant effect of conventional learning methods with an average increase of 7.93 with a significant level of 0.05. There is a significant effect of the Drill learning method with an average increase of 9.57 with a significant level of 0.05. There is a difference of influence between Conventional learning methods and Drill learning methods by showing differences or the difference in the average value of 1.633. thus showing that the Drill learning method has a very good effect compared to the conventional learning method.Keywords: Drill method, student learning outcomes, under pass, volleyball, junior high school Penelitian ini bertujuan untuk mengetahui pengaruh antara metode pembelajaran Drill dan metode pembelajaran konvensional terhadap hasil belajar passing bawah permainan bola voli siswa SMPN 2 Mare Kabupaten Bone. Metode penelitian ini merupakan jenis penelitian eksperimen yang dipilih secara random sampling kemudian diberi pretest dan posttest dengan populasi semua siswa SMPN 2 Mare Kabupaten Bone. Selanjutnya dipilih kelas VIIIA dan kelas VIIIB untuk menjadi sampel penelitian ini yang jumlahnya masing – masing 30 orang siswa kemudian dibagi menjadi dua kelompok dengan menggunakan maching ordinal paired. teknik analisis data yang digunakan uji t dengan taraf signifikan 0.05. Hasil penelitian ini menujukkan ada pengaruh yang signifikan metode pembelajaran konvensional dengan peningkatan rata rata 7,93 dengan taraf signifikan 0,05. Ada pengaruh yang signifikan metode pembelajaran Drill dengan peningkatan rata rata 9.57 dengan taraf signifikan 0,05. Ada perbedaan pengaruh antara metode pembelajaran Konvensional den metode pembelajaran Drill dengan menunjukkan perbedaan atau selisih nilai rata rata 1,633. sehingga menunjukkan metode pembelajaran Drill memiliki pengaruh yang sangat baik dibanding metode pembelajaran Konvensional.Kata kunci: Metode Drill, hasil belajar siswa, pasing bawah, bola voli, SMP